Use of Carbon Compounds (Carbon Nanotubes and Activated Carbon) in theImprovement of TiO2–Carbon Supercapacitor Performance - Sudarto, Joko; Subagio, Agus; Priyono,; Pardoyo,; Yudianti, R.; Subhan, (UI Scholars Hub, 2019)
Improvement ofthe performance of titanium oxide (TiO2)–carbon supercapacitor was studied by fabricating a double-layer electrode compositeconsistingof (TiO2), activated carbon(AC), and carbon nanotubes (CNTs). A thin layer of TiO2/CNT/AC electrode was coated on an aluminum foil substrate through the addition of a polyvynilidene fluoride adhesive of around 15% of the total weight of the composite. The resultant layer was then made into a double layer, and its conductivity and capacitance were measured using the electrochemical impedance spectroscopy (EIS). Results showed that the supercapacitor performance improved with the addition of CNTs. The highest performance was obtained with a composition of 23.3% TiO2, 21.0% CNT, and 4.0% AC with a 1.29×10-2 S/m conductivity and 5.56 F/g capacitance (C) at a frequency of 0.1 Hz.